2018
DOI: 10.1111/dme.13567
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impacts of hybrid closed‐loop systems in the management of diabetes: a review

Abstract: There is a pressing need for new treatment regimens that enable improved glycaemic control and reduced diabetes self-management burdens. Closed-loop, or artificial pancreas, systems represent one of the most promising avenues in this regard. Closed-loop systems connect wearable continuous glucose monitor (CGM) sensors to smartphone- or tablet-mounted algorithms that process and model CGM data to deliver precise and frequently updated doses of fast-acting insulin (and glucagon in dual-hormone systems) to users … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 52 publications
2
77
1
1
Order By: Relevance
“…Previous studies have suggested a reduction in psychosocial burden 10 and improved glycaemic control 11 with closed-loop systems. Similar benefits have been reported with OpenAPS, initially in 2016 12 and more recently this year at the 78th scientific sessions of the American Diabetes Association.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested a reduction in psychosocial burden 10 and improved glycaemic control 11 with closed-loop systems. Similar benefits have been reported with OpenAPS, initially in 2016 12 and more recently this year at the 78th scientific sessions of the American Diabetes Association.…”
Section: Discussionmentioning
confidence: 99%
“…The psychosocial benefits of closed‐loop have been explored in older children, adolescents, and adults but the impact of closed‐loop use in very young children with type 1 diabetes is yet to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…6 While highly specific to 670G systems, these data nevertheless echo previous psychosocial research reporting burdens as well as benefits for closed-loop users. 7 While 670G and (increasingly) home-made closed-loop systems are used by growing numbers of users, national and international eligibility guidelines have yet to be formulated. 8 Consequently, while the automated nature of closed-loop technology promises improved control for people with type 1 diabetes, debate continues regarding appropriate levels of closed-loop usage in mainstream care.…”
Section: Introductionmentioning
confidence: 99%